岩手県における東日本大震災被災瓦礫集積場におけるハエ類発生調査（2012年） - 澤辺, 京子; 林, 利彦 (Medical entomology and zoology, 2016)
We surveyed the fly emergence at 2 places of processing yards for disaster debris in Iwate Prefectrue in 2012 using sticky traps. After the tsunami of 2011 the Great East Japan Earthquake, a lot of flies were emerged and caused problem, but mass occurrence of flies were not observed there in 2012.